Energy and exergy evaluation of triple-effect H2O/LiBr absorption cooling system. Issue 1 (31st December 2022) - Solanki, Alka; Pal, Yash
Abstract : This paper deals with the energy and exergy analysis of triple-effect LiBr–water absorption system. Mathematical models have been developed using an engineering equation solver (EES) to simulate the triple-effect absorption cycle. The coefficient of performance, exergy efficiency and total exergy destruction are determined by varying generator, absorber and evaporator temperatures. The operating parameters are selected as generator temperature (170–200°C), absorber temperature (25–40°C) and evaporator temperature (5–11°C). Findings illustrate that COP of triple-effect absorption cycle increases at absorption temperatures 35°C and 40°C. For a given evaporator and generator temperature, COP and exergy efficiency of triple absorption cycle increase. The total exergy destruction rate decreases with an increase in evaporator temperature. Largest exergy destruction and exergy percentage are found in absorber and smallest in medium pressure generator.